The theatre of Societas Raffaello Sanzio - Castellucci, Claudia; Castellucci, Romeo; Guidi, Chiara; Kelleher, Joe; Ridout, Nicholas (London : Routledge, 2007)
The Theatre of Socìetas Raffaello Sanzio chronicles four years in the life of an extraordinary Italian theatre company whose work is widely recognized as some of the most exciting theatre currently being made in Europe. At the centre of the book is a detailed exploration of the company's eleven episode cycle of tragic theatre, Tragedia Endogonida (2002–2004,) including: •production notes and extensive correspondence giving insights into the creative process •essays by and conversations with company members alongside critical responses by their two co-authors •seventy-two photographs of the company's work. This is a significant collection of theoretical and practical reflections on the subject of theatre in the twenty-first century, and an indispensible written and visual document of the company's work.
boek
Keywords: Societas Raffaello Sanzio; Del Pia, Luca